2017
DOI: 10.1002/mds.26896
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in leucine‐rich repeat kinase 2‐associated Parkinson's disease

Abstract: Heart rate variability may remain intact in LRRK2-associated PD, adding to a growing literature supporting clinical-pathologic differences between LRRK2-associated and idiopathic PD. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
(84 reference statements)
2
13
0
Order By: Relevance
“…Although no significant GWAS hit was found in a large series of pathologically confirmed MSA cases, some interesting findings involving a mixed MSA pathology have been reported. The SNCA p.Gly51Asp mutation was found in families presenting with autosomal‐dominant parkinsonism with autopsy findings typical for both PD and MSA . Similar pathology findings were also observed in a family with the p.Ala53Glu mutation .…”
Section: Autonomic Dysfunction In Familial Pd Vs Msa and Ipdsupporting
confidence: 64%
See 1 more Smart Citation
“…Although no significant GWAS hit was found in a large series of pathologically confirmed MSA cases, some interesting findings involving a mixed MSA pathology have been reported. The SNCA p.Gly51Asp mutation was found in families presenting with autosomal‐dominant parkinsonism with autopsy findings typical for both PD and MSA . Similar pathology findings were also observed in a family with the p.Ala53Glu mutation .…”
Section: Autonomic Dysfunction In Familial Pd Vs Msa and Ipdsupporting
confidence: 64%
“…The [ 18 F]fluorodopamine PET scan showed absent myocardial radioactivity, despite approximately normal perfusion on 13 N ‐ammonia scanning consistent with loss of sympathetic nerves in the left ventricle. Similarly, other patients with PD and OH attributed to p.Ala53Thr or SNCA triplications had higher rates of cardiac 6‐[18F]‐dopamine loss when compared to patients with iPD and OH …”
Section: Familial Pd and Autonomic Dysfunctionmentioning
confidence: 87%
“…Several hub-genes involved directly or indirectly that regulate the nervous system were found among AF-DEGs. Visanji’s group compared resting electrocardiograms of LRRK2 -associated Parkinson’s disease (PD) patients, nonmanifesting carriers, noncarriers, and idiopathic PD patients to investigate heart rate variability in LRRK2 -associated PD [24]. There is evidence that LRRK2 may act as a biofunctional mediator to correlate heart rate variability and PD [24].…”
Section: Discussionmentioning
confidence: 99%
“…Visanji’s group compared resting electrocardiograms of LRRK2 -associated Parkinson’s disease (PD) patients, nonmanifesting carriers, noncarriers, and idiopathic PD patients to investigate heart rate variability in LRRK2 -associated PD [24]. There is evidence that LRRK2 may act as a biofunctional mediator to correlate heart rate variability and PD [24]. In a molecular mechanistic study, the neural protective role for regulating mitochondrial complex I function and oxidative stress in ischemia/reperfusion was identified [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Non-motor features and early predictors of PD also include reduced heart-rate variability (HRV) and cardiac sympathetic neurodegeneration [71,72]. In a study using classic HRV parameters, there was no difference between LRRK2-PD and healthy controls [73]. However, a follow-up study of the same cohort analyzed novel HRV parameters and showed that there is more vagal involvement in LRRK2-PD and even in a subset of LRRK2 nonmanifesting carriers suggesting a pre-clinical endophenotype of impairment of cardiac innervation [74].…”
Section: Motor and Non-motor Features In Lrrk2-pdmentioning
confidence: 99%